2011
DOI: 10.1029/2011gc003698
|View full text |Cite
|
Sign up to set email alerts
|

Viscous coupling at the lithosphere-asthenosphere boundary

Abstract: [1] Tectonic plate motions reflect dynamical contributions from subduction processes (i.e., classical "slabpull" forces) and lateral pressure gradients within the asthenosphere ("asthenosphere-drive" forces), which are distinct from gravity forces exerted by elevated mid-ocean ridges (i.e., classical "ridge-push" forces).Here we use scaling analysis to show that the extent to which asthenosphere-drive contributes to plate motions depends on the lateral dimension of plates and on the relative viscosities and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 58 publications
6
84
0
Order By: Relevance
“…The assumption of a strong dehydrated lithosphere above a low-viscosity channel in the upper mantle allowed for channelization of lateral flow in the weak upper mantle [Höink et al, 2011]. Without channels, convective stresses driving failure would be smaller (see Figures 5 and 8 and Table 2, which show that decreasing channel thicknesses lead the systems from stagnant lid over episodic to plate tectonics).…”
Section: Channels Matter But Novel Causality Results Remain Robustmentioning
confidence: 99%
See 4 more Smart Citations
“…The assumption of a strong dehydrated lithosphere above a low-viscosity channel in the upper mantle allowed for channelization of lateral flow in the weak upper mantle [Höink et al, 2011]. Without channels, convective stresses driving failure would be smaller (see Figures 5 and 8 and Table 2, which show that decreasing channel thicknesses lead the systems from stagnant lid over episodic to plate tectonics).…”
Section: Channels Matter But Novel Causality Results Remain Robustmentioning
confidence: 99%
“…Our results support those ideas, and we did observe hot rising instabilities, from the lower thermal boundary layer, interacting with the upper boundary layer. We also observed that lateral temperature variations, in the low-viscosity upper mantle, could generate pressure gradients that drove lateral flow [Höink et al, 2011] and this, in turn, influenced upper boundary layer dynamics. Both of these effects are not consistent with the idea that the dynamics of the boundary layer are fully self determined.…”
Section: The Limits Of Self-determined Boundary Layer Dynamicsmentioning
confidence: 88%
See 3 more Smart Citations